Differential cardiac impacts of hematological malignancies and solid tumors: a histopathological and biomarker study - Michael H. Udin; Sunitha Shyam Sunder; Sarmila Nepali; Sharma Kattel; Amr Abdelradi; Scott T. Doyle; Ciprian N. Ionita; Qian Liu; Umesh C. Sharma; Saraswati Pokharel (Cardio-Oncology)
Abstract Background Cancer patients are known to be associated with increased risk of cardiovascular disease. However, no studies have examined the differential impact of hematologic malignancies (HMs) and solid tumors (STs) on cardiac morphology at the tissue level. Objective We aimed to examine histopathological features alongside cardiovascular biomarkers in patients with HMs and STs who underwent post-mortem evaluation. Methods We analyzed cardiac changes in 198 patients with HMs and 164 patients with solid tumors STs. We compared demographics, echocardiogram data, exposure to various antineoplastic agents, and post-mortem findings. Additionally, cardiac histological validation was conducted on post-mortem cardiac specimens to examine cardiac tissue morphology, focusing on cardiomyocyte nuclear density, collagen content, and collagen fiber orientation. Results HM patients displayed significantly disordered collagen fiber alignment (0.71 vs 0.83, P = 0.027), and reduced cardiomyocyte nuclear density (56 vs 72, P = 0.002) compared to ST patients. Similarly, hemoglobin level was decreased (6.71 vs 8.06, P < 0.001) in HM patients compared to ST patients. HM patients also showed elevated B-type natriuretic peptide levels (2,275 vs 867, P < 0.001), without significant differences in creatine-kinase MB and cardiac troponin levels. Multivariate analysis identified increased right ventricular thickness, low diastolic blood pressure, and high cardiac troponin levels as risk factors for cardiac death in HM patients. Conclusions This study demonstrates that HM patients have fewer cardiomyocyte nuclei and poorly aligned collagen, with serum biomarker evidence of increased cardiac dysfunction. This supports the necessity for specialized cardiac care for these patients.